Comparison of Leaf Reflectance of Sorghum Plants Infested by Sugarcane Aphids - Dick, Nathaniel; Bhattarai, Ganesh P.; McCornack, Brian (My University, 2018)
Sugarcane aphid, Melanaphis sacchari (Homiptera: Aphididae; Fig. 1A), is a significant pest to sorghum, Sorghum bicolor (Fig. 1B). Sorghum fields are regularly surveyed to detect pest infestation. Remote sensing methods using satellite and aircraft data are expected to provide an efficient alternative to field surveys. However, spectral signature of sugarcane aphid infested sorghum plants is not well understood. We evaluated reflectance spectra of sorghum leaves infested by sugarcane aphids. We used those spectral data to estimate indices that are related to photosynthetic pigments such as chlorophyll', anthocyanin, and carotenoids. We also estimated an aphid index, damage sensitive spectral index (DSSI)". We used these data to examine whether indices differ between pest infested and uninfested plants. We predicted that plants infested by aphid will have higher levels of anthocyanin, carotenoids, and DSSI indices compared to the control plants. In contrary, chlorophyll index will be greater for uninfested plants.
Keywords: Fall 2018